Iatrogenic Injury to the Suprascapular Nerve Following Reverse Shoulder Arthroplasty: A Case Report. (August 2022) - Long, Jason; Liles, Jordan; Anakwenze, Oke; Klifto, Christopher
The location and course of the suprascapular nerve (SSN) to the glenohumeral joint places this nerve at risk when operating around the shoulder. Iatrogenic injury to the suprascapular nerve has been described in several different procedures including, rotator cuff repairs, posterior capsulorraphy, Bankart repairs, SLAP lesion repairs, Latarjet procedures, and shoulder arthroplasty. We present a case of iatrogenic suprascapular nerve injury due to superior glenoid baseplate screw placement following primary reverse shoulder arthroplasty (RSA), a novel approach to diagnosis of nerve injury, and treatment.